Detecting Post-nuclear Crisis in Hanna Jameson's The Last - Renáta Zsámba (Acta Universitatis Sapientiae: Philologica)
. Hanna Jameson’s post-apocalyptic detective novel, The Last (2019), addresses contemporary issues that affect us on both a collective and an individual level. The author diagnoses the denial of nuclearism and calls for an awareness of the nuclear age combined with the looming threat of climate change. The novel negotiates alternative strategies for the treatment of crisis brought about by the nuclear attack and borrows many of the thematic and structural elements from twentieth-century nuclear fictions in which the apocalypse is not necessarily regarded in negative terms but as a chance for regeneration. The events of the post-nuclear months in a Swiss hotel are narrated by an American historian whose written account serves several goals. It gives the illusion of delaying crisis, but it also reveals his fears and traumas conjured up by radioactive spectres. There are two different types of narratives at work, the narrative of the crisis and that of the investigation. The narrator-protagonist becomes obsessed with finding the solution to a murder mystery, which in a metaphorical sense is to give a soothing answer to the death of millions. However, this attempt keeps failing, and thus the narrative of the crisis devours all kinds of rational initiatives to resolve chaos. In order to elaborate on the psychological impact of the post-nuclear crisis in subject construction, I do not only examine the character of the amateur detective of the whodunit whose intervention aims to restore order, but I also apply Gabriele Schwab’s concepts of post-nuclear subjectivity and nuclear hauntology.